RANCANG BANGUN SISTEM KENDALI PID UNTUK INTENSITAS CAHAYA LAMPU DC MENGGUNAKAN MIKROKONTROLER ARDUINO UNO - Tanza, Nendya Ertika; Sumariyah, Sumariyah (BERKALA FISIKA, 2019)
The design of PID (Proportional Integral Derivatives) control system has performed for DC light intensity using an Arduino Uno microcontroller. This research aims to create a DC light intensity control system automatically using Arduino Uno, test the design light intensity control system using PID control and test the stability response of the light intensity control system before and after being given interference in the form of obstructions and external light. The method used in this research is Ziegler-Nichols 1 method to obtain the PID constant. The BH1750 sensor is converted to a digital signal by the BH1750 converter and transmitted to the Arduino Uno microcontroller chip via the I2C interface. The PID constant resulting from the Ziegler-Nichol method approach is used for the experimental approach to manual tuning and determining the cycle of Pulse Width Modulation (PWM). The results of this research obtained 82,42% system accuracy and PID constant, is KP = 0,1; KI = 2,0 andKD = 0,00000102. The built-in lamp light intensity control system is able to stabilize due to interference in an average time of 1 second at 400 lx setpoint.Keywords : BH1750, DC lights, microcontroler, PID, PWM